2009
DOI: 10.1038/ejcn.2009.135
|View full text |Cite
|
Sign up to set email alerts
|

Using restrictive messages to limit high-fat foods or nonrestrictive messages to increase fruit and vegetable intake: what works better for postmenopausal women?

Abstract: Background/Objectives: To compare the effects of two dietary approaches on changes in dietary intakes and body weight: (1) an approach emphasizing nonrestrictive messages directed toward the inclusion of fruits and vegetables (HIFV) and (2) another approach using restrictive messages to limit high-fat foods (LOFAT). Subjects/Methods: A total of 68 overweight-obese postmenopausal women were randomly assigned to one of the two dietary approaches. The 6-month dietary intervention included three group sessions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
(37 reference statements)
2
11
0
Order By: Relevance
“…15,16,29 However, by examining the variation in actual vegetable intake across the study sample, we confirmed similar reported findings 11 that vegetable intake correlated with weight loss (Figure 3). The shifts in macronutrient profile were consistent with an increase in the relative amount of vegetables in a dietary pattern comprising core staple foods, as was advised.…”
Section: Discussionsupporting
confidence: 87%
“…15,16,29 However, by examining the variation in actual vegetable intake across the study sample, we confirmed similar reported findings 11 that vegetable intake correlated with weight loss (Figure 3). The shifts in macronutrient profile were consistent with an increase in the relative amount of vegetables in a dietary pattern comprising core staple foods, as was advised.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of a relationship between FVs and SFs is consistent with previous research in adults [3,8] and children at-risk for obesity [9]. Results of this study suggest while increasing FVs may increase the nutrient quality of the diet, as FVs are nutrient-dense foods, increasing FVs may not automatically reduce intake of high-energy-dense, non-nutrient-dense foods or energy intake.…”
Section: Discussionsupporting
confidence: 88%
“…Of the studies conducted mixed results have been found. Several studies were unable to find a significant relationship between consumption of FVs and SFs [3,8,9] while other studies do demonstrate a relationship between intake of FVs and SFs [10,11]. For those studies suggesting that an increase in FVs is related to a decrease in energy-dense foods, analyses have examined changes in dietary intake across time.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore one study reported significant decreases in body weight post-intervention (Lapointe et al, 2010). Dietary intake data from this study showed decreases in energy intakes (-90 kcals) and fat intakes (-2%), however these did not reach statistical significance.…”
Section: Analysis Of Findings For Systematic Reviewmentioning
confidence: 61%